The Policy on the Determination of Top-Up Fee of E-Money - Fadia Fitriyanti; Muhammad Arif Hartavian (Jurnal Hukum Novelty, 2021)
Introduction to The Problem: Bank Indonesia (BI) has determined the top-up fee of e-money in the Board Governor Member Regulation Number 19/8/PADG/2017 on the National Payment Gateway. This regulation is contrary to article 2 paragraphs 2, article 23 paragraph 1, article 33 paragraph 2 Law Number 7 of 2011 concerning Currency expressly regulates that every person is prohibited from refusing to accept rupiah. Aside from that, the regulation has the potential to cause injustice and discrimination for consumers.Purpose/Objective Study: This research aims to analyze whether Bank Indonesia actions determine the top-up fee in the form of the Board Governor Member Regulation Number 19/8/PADG/2017 on the National Payment Gateway are in line with its duties and authorities.Design/Methodology/Approach: This research uses the normative legal research type with the statute approach to research the Legislation that regulates Bank Indonesia authority regarding the policy on a top-up fee issued by Bank Indonesia supervision on implementing its policy.Findings: The research concluded that there is an inconsistency authority between Bank Indonesia and Financial Service Authority. Bank Indonesia is authorized to regulate the top-up fee of e-money to ensure consumer protection and the payment systems smoothness. Moreover, the supervision regarding the e-money top-up fee was in the hand of Bank Indonesia. However, when the consumer suffered loss because of the e-money organizers fault, the Financial Service Authority could take the lead to facilitate the customers complaint.Paper Type: Research Article.